Simplified and refined methods for seismic vulnerability assessment and retrofitting of an Italian cultural heritage masonry building. (February 2017) - Formisano, A.; Marzo, A.
Abstract: In the paper the usability check and the seismic vulnerability appraisement and repairing of a masonry building with cultural and artistic value located in the Municipality of Cento (Ferrara, Italy) after the last Italian seismic events (Emilia-Romagna, 2012 May 20th and 29th), are reported and discussed. After some indications on the mentioned earthquakes are given, the case study has been presented and useful information on both historical news and geometrical properties have been given. So, the usability check of examined building has been done through the identification of damages occurred under earthquake. Later on, seismic vulnerability assessment of the building on the basis of both the simplified LV1 and the refined LV3 analysis levels given by Italian Guidelines on Cultural Heritage has been performed. The analysis results, compared each other in terms of seismic safety factors, have shown that building has an average vulnerability degree, so to require local repairing and strengthening interventions, which have been herein presented. Finally, the effectiveness of the proposed local interventions has been proved by numerical analysis in the non-linear field.